2013
DOI: 10.1002/hep.26222
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic-specific activation of peroxisome proliferator-activated receptor γ coactivator-1β protects against steatohepatitis

Abstract: Development of hepatic steatosis and its progression to steatohepatitis may be the consequence of dysfunction of several metabolic pathways, such as triglyceride synthesis, very low-density lipoprotein (VLDL) secretion, and fatty acid b-oxidation. Peroxisome proliferator-activated receptor c coactivator-1b (PGC-1b) is a master regulator of mitochondrial biogenesis and oxidative metabolism, lipogenesis, and triglyceride (TG) secretion. Here we generated a novel mouse model with constitutive hepatic activation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(59 citation statements)
references
References 33 publications
3
55
0
1
Order By: Relevance
“…A growing body of data shows a biological role of miR-378a-3p in a variety of diseases [27,28]. In cancer, miR-378a suppresses the growth of hepatitis B virus-related hepatocellular carcinoma by targeting the insulin-like growth factor 1 receptor [27].…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of data shows a biological role of miR-378a-3p in a variety of diseases [27,28]. In cancer, miR-378a suppresses the growth of hepatitis B virus-related hepatocellular carcinoma by targeting the insulin-like growth factor 1 receptor [27].…”
Section: Discussionmentioning
confidence: 99%
“…PGC-1β and transducin beta-like 1 (TBL) also serve as PPARα coactivators. Hepatocyte-specific overexpression of PGC-1β increases the expression of β oxidative genes and protects PGC-1β transgenic mice from diet-induced steatosis (12). Knockdown of TBL1 or its partner TBLR1 in the liver inhibits PPARα activity, decreases β oxidation and ketogenesis, and promotes hepatic steatosis (117).…”
Section: Liver Fatty Acid Metabolismmentioning
confidence: 99%
“…To better understand the contributions of either of these isoforms to phenotype, a liver-specific double-KO mouse model should be analyzed. A PGC-1␤ liver-specific overexpression model under the control of apolipoprotein E promoter has shown that PGC-1␤ overexpression protects against steatohepatitis through increased oxidative metabolism, ␤ oxidation and triglyceride secretion [114].…”
Section: Pgc-1α In Livermentioning
confidence: 99%